The Effects of Culture on Active and Passive Reactions to Financial Offenders; the Moderating Role of Type of Harm - Fousiani, Kyriaki (Victims & offenders, 2023)
In the present research, we examine how culture influences individuals’ reactions to financial offenders. We hypothesized that horizontal individualists deploy increased active reactions (i.e., punishment-oriented) whereas vertical collectivists deploy increased passive reactions (i.e., condemning beliefs) to financial offenders. Moreover, we hypothesized that horizontal individualists would react stronger to a financial offender when an offense has instrumental (i.e., related to material costs) as opposed to symbolic (i.e., related to one’s self-image) implications for a victim, while vertical collectivists would show the opposite pattern of results. In Studies 1 and 2 we directly compared British (i.e., a horizontal individualist culture) versus Greek (i.e., a vertical collectivist culture) participants. Study 3 aimed to replicate Studies 1 and 2 by measuring cultural values at the individual level. The results obtained in the three studies provided support for most of our hypotheses. Theoretical and practical implications are discussed.